Localization of fibroblast growth factor 23 protein in the rat hypothalamus - Ursem, Stan R. (2021)
Endocrine Laboratory, Department of Clinical Chemistry, Amsterdam Gastroenterology & Metabolism, Amsterdam UMC, Vrije Universiteit Amsterdam and University of Amsterdam.Amsterdam, The Netherlands.